2020
DOI: 10.1038/s41598-019-55107-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation does not prevent the recurrence of Graves’ disease

Abstract: Recent literature has reported a higher prevalence of vitamin D deficiency among people with Graves' disease. No study has examined the effect of vitamin D supplementation on the clinical outcomes of Graves' disease. We aimed to evaluate whether daily vitamin D supplementation reduces Graves' disease recurrence. We enrolled 210 subjects with Graves' disease and vitamin D deficiency and followed them for at least one year after anti-thyroid drug (ATD) discontinuation. Among 210 individuals, 60 (29%) were amenab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Some recent studies evaluated the effects of VitD supplementation and outcomes in GD. Supplementation may delay the onset, but does not seem to prevent disease recurrence [102]. This intervention may have beneficial effects on cardiovascular outcomes (as suggested by a reduction in pulse wave velocity), which are limited to patients with VitD deficiency [103].…”
Section: Relevance Of Supplementationmentioning
confidence: 99%
“…Some recent studies evaluated the effects of VitD supplementation and outcomes in GD. Supplementation may delay the onset, but does not seem to prevent disease recurrence [102]. This intervention may have beneficial effects on cardiovascular outcomes (as suggested by a reduction in pulse wave velocity), which are limited to patients with VitD deficiency [103].…”
Section: Relevance Of Supplementationmentioning
confidence: 99%
“…Supplementation with vitamin D (cholecalciferol) has become a widely used practice, since a relationship has been demonstrated of low levels of this nutrient with the increased risk of cardiovascular diseases, the recurrence of diseases, and mortality 1 , 2 , 3 . However, as there is no consensus on sufficient serum levels of vitamin D, taking into account its non-skeletal functions, it is necessary to assess whether the increase in this nutrient in individuals with 25-hydroxyvitamin D (25 (OH) D) levels above the current cut-off point, generates any health benefits 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Our study also found that only a few bacterial taxa, such as the dominant bacterial- Proteobacteria , Acidobacteria , Actinobacteria , and Chloroflexi ( Figure 5 A), were in the plant rhizosphere and bulk soil. In other reports, these abundant bacterial taxa in the bulk and rhizosphere soil were dominant as well [ 52 , 53 ]. Furthermore, the taxa of Cyanobacteria in endophytes were much higher ( Figure 5 B).…”
Section: Discussionmentioning
confidence: 55%